2013
DOI: 10.1534/genetics.113.154948
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Divergence in Experimental Populations ofPseudomonas fluorescens. V. Insight into the Niche Specialist Fuzzy Spreader Compels Revision of the ModelPseudomonasRadiation

Abstract: Pseudomonas fluorescens is a model for the study of adaptive radiation. When propagated in a spatially structured environment, the bacterium rapidly diversifies into a range of niche specialist genotypes. Here we present a genetic dissection and phenotypic characterization of the fuzzy spreader (FS) morphotype-a type that arises repeatedly during the course of the P. fluorescens radiation and appears to colonize the bottom of static broth microcosms. The causal mutation is located within gene fuzY (pflu0478)-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 87 publications
2
68
0
Order By: Relevance
“…SM and WS genotypes appear to correspond to two potentially overlapping clusters in niche space. Recent work indicates the same holds for the niches of WS and fuzzy spreader genotypes (47).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…SM and WS genotypes appear to correspond to two potentially overlapping clusters in niche space. Recent work indicates the same holds for the niches of WS and fuzzy spreader genotypes (47).…”
Section: Discussionmentioning
confidence: 82%
“…Coexistence among WS genotypes has also been shown to be stabilized by negative frequency-dependent fitness interactions, indicating differences between their niches (41). The genetic changes underlying this model of adaptive radiation have been established for various niche specialists at the nucleotide level (40,(42)(43)(44)(45)(46)(47).…”
Section: Resultsmentioning
confidence: 94%
“…Diversification of SM SBW25 (Figure 4a) showed a typical pattern with WS arising on day 3 and Fuzzy Spreader (FS) types at day 4 (Ferguson et al, 2013). Interestingly, CC types were detected on day 1 but never increased beyond a small fraction.…”
Section: Evolutionary Convergencementioning
confidence: 97%
“…When a mixture of carbon sources was offered (glucose and citrate; glucose and tryptone), no aggregation was observed. As earlier studies reported an influence of the pH on the aggregate formation (Ferguson et al 2013), glucose-containing media were tested in the pH range of 6.4-8.0. Here, no effect of the pH on the aggregation behaviour of the Fig.…”
Section: Autoaggregation Is Carbon Source Dependentmentioning
confidence: 99%